(untitled) (Applied Research and Innovation, 2023)
This study was undertaken to redesign, fabricate, and evaluate the performance of animal-drawn seed drill prototype capable of drilling wheat and barley seeds and applying fertilizer at predetermined row spacing and depths. The physical properties of seeds involved in the study were investigated to optimize the design of the seed drill’s components. The developed seed drill machine, consists of a frame, seed and fertilizer hopper, seed metering devices, seed delivery tube, adjustable furrow opener, and drive wheels. The performances were evaluated in terms of Seed and fertilizer rate, row spacing, depth of seed placement, plant count/stand, field capacity and field efficiency. The investigation revealed that the sphericity of Hidase, Digelu, Ogolcho, and Kekeba wheat varieties were 65.81 %, 64.79% and 62.62 %, respectively. Row-to-row spacing can be 20 cm and depth also adjustable to 5 to 7 cm as per wheat agronomic requirements. The developed four row animal drawn seed drill was tested in the laboratory and field. The seed rate was calibrated and observed that 127 kg/ha with a middle flap position adjustment lying in the acceptable range of the recommended seed rate. There was no visible damage observed. The mean field capacity and field efficiency were 0.112 ha/hr and 81.78% at speed of 1.71km/hr. 310 to 318 plant populations per meter square (1 m2) area were observed during field germination count. Based on the performance evaluation results, it is concluded that the developed seed drill can be effectively and economically used by most farmers.